SISTEM PAKAR DIAGNOSA KERUSAKAN MOTOR 4 TAK HONDA VARIO DENGAN ALGORITMA C4.5 - Baktiar Setiyaji; Teguh Susyanto; Dwi Remawati (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2018)
Users of motorcycle vehicles more and more, it is necessary a system that can help motorcycle users to solve the problem of damage that occurred on the motorcycle especially Honda Vario in 2006 -2013. The system is knowledge-based to identify motorcycle damage that is displayed using a web-based programming language. The research method for this expert system using algorithm C4.5 Algorithm C4.5 is to form decision tree and used to classify damage become damage which most influence motor to light damage. The resulting output is the creation of a system that can help the user for the initial handling that occurs on a motorcycle and is expected to accelerate the repair of a motorcycle classified as minor damage.Keywords: Diagnose the Damage, Algorithm C4.5, Expert System, Motorcycle